A study of four key aspects within five bargaining councils over the period 1995 to 2010 - Holtzhausen, M M E (Department of Sociology, 2015)
The research focused on bargaining councils in five industries as statutory institutions for centralised collective bargaining. The purpose was to determine how bargaining councils adapted to the changing environment during the 15-year period from 1995 to 2010, with a particular focus on representivity, the main agreement (wages and conditions of service), benefit funds, dispute resolution and other related developments.